Network Planning Analysis on Road Construction Projects by CV. X Using Evaluation Review Technique (PERT)-Critical Path Method (CPM) and Crashing Method - Farida, Yuniar; Anenda, Lulitasari Putri (International Journal of Integrated Engineering, 2022)
Indonesia is currently actively developing infrastructure to improve the economy and welfare of its people. One of the infrastructure developments undertaken by the government is road pavement. CV.X is the company that won the asphalt project tender with a contract value of IDR 4.046.873.346 and must complete it within 114 days. During the process of working on the project, there were indications of possible delays in project completion. So this study aims to perform optimal planning, scheduling, and control in CV. X in carrying out road construction project. This study used the PERT – CPM method to determine the optimal completion time using critical pathways and the concept of probability. The result of the PERT – CPM method is an activity in critical flow with an optimal duration of 115 days, where the duration exceeds the contract period so it needs to be crashing. The crashing method is an attempt to speed up the duration of the project and streamline the costs incurred. In this study, 2 scenarios were obtained to help reduce the duration and cost savings that can be used by project implementers. The first scenario is to reduce the duration based on the optimal duration from 115 days to 108 days with a saving of IDR 690,354 or 0,02%. The value of the savings is classified as very small because crashing can only be done with additional labor and limited working hours. If the crashing method is not done, then the second scenario is to pay a penalty of IDR 40,468,733.